Increasing Saudi women's participation in professional occupations: a Saudi perspective - Alselaimi, Raneem Abdul Wahab A (Curtin University, 2014)
This research endeavours to provide a deeper understanding of the Saudi male-dominated system that is embedded in the Saudi social and cultural spheres. In particular, the thesis examines the different layers of meaning interconnected to each other which affect the Saudi system and the system’s ability to provide equal opportunities for both male and female nationals.